An Analysis of Driving Factors of Collaboration in Handling Used Cell Phones as a Waste Management Practice - Siti Mahsanah Budijati; I Nyoman Pujawan; Hayati Mukti Asih (Salehan Institute of Higher Education, 2022)
The handling of used cell phones in Indonesia is mostly carried out by informal actors, starting from second-hand market actors. However, the activities of the informal actors often endanger the environment and human health. To reduce the impact, some of the activities should be transferred to formal parties. This requires collaboration of both parties as a form of waste management, which previously has never been established. The objective of this study is to explore the driving factors of collaboration intention of informal actors in handling used cell phones with the formal ones. Data were collected using questionnaires distributed to second-hand market actors in five districts in the Special Region of Yogyakarta Province. In this study, three internal driving factors are considered, which are environmental attitude, management commitment, and financial benefits, as well as two external driving factors: government support and competitor pressure. The regression analysis in each region revealed that the most significant driving factors vary across different regions, such as government support in Gunungkidul, management commitment in Bantul, competitive pressure and government support in Kulonprogo, government support, management commitment, and financial benefit in Sleman, as well as environmental attitude and financial benefit in Yogyakarta City. From the structural equation modeling at the provincial level, it was found that financial benefit and government support were the most significant factors influencing the collaboration intentions of all informal actors. The results of this study can be used as a reference. Doi: 10.28991/CEJ-2022-08-10-016 Full Text: PDF